Mise en parallèle des dimensions linguistiques et prosodiques de l’ironie - Baklouti, Elodie; Hirsch, Fabrice (Neophilologica, 2016)
As part of this paper we want to question the possible link between prosody and linguistic realization of irony. In other words, we want to determine if the speaker who utters an ironic statement transmits prosodic signals to allow his interlocutor to recognize the irony. Indeed, in the literature on the subject, many authors believe that, in some contexts, prosody is the only indication of the interlocutor’s recognition of irony (Eggs, 2009 for ex.). Some researchers even speak of intonation peculiar to irony (Fonagy, 1991). The existence of this specific intonation, however, has never been demonstrated, as no real consensus exists on the subject in the literature. Thus, Bryant and Tree (2005) showed that only rhythmic aspects play a major role in the production of an ironic statement. According to these, a slower speed would be the only prosodic feature associated with irony. To verify or refute these assumptions and assess the nature of the relationship that may exist between prosody and linguistic realization of irony, we intend to base our argument on an experiment conducted on a group of speakers we asked to read a statement categorized as ironic, then we asked them to read the same statement categorized as neutral.